Whistler - Spencer, Robin (New York : Portland House, distributed by Crown Publishers, 1990)
Text and 48 annotated reproductions of Whistler's key works set the Whistler phenemenon in the context of 19th century art.
Originally published by Studio Editions Ltd.
Spine title: Whistler, the masterworks.
Includes bibliographical references (page 140).
Keywords: Whistler, James McNeill, -- 1834-1903.; Whistler, James McNeill, -- 1834-1903